(untitled) (Almanack, 2021)
Resenha de: SILVA, Leandro Ferreira Lima da. Regalismo no Brasil colonial: a Coroa portuguesa e a Ordem do Carmo, Rio de Janeiro, 1750-1808. São Paulo: Intermeios: USP; Brasília: CAPES, 2018.